2020
DOI: 10.1051/0004-6361/202037685
|View full text |Cite
|
Sign up to set email alerts
|

The Fornax 3D project: Globular clusters tracing kinematics and metallicities

Abstract: Globular clusters (GCs) are found ubiquitously in massive galaxies and due to their old ages, they are regarded as fossil records of galaxy evolution. Spectroscopic studies of GC systems are often limited to the outskirts of galaxies, where GCs stand out against the galaxy background and serve as bright tracers of galaxy assembly. In this work, we use the capabilities of the Multi Unit Explorer Spectrograph (MUSE) to extract a spectroscopic sample of 722 GCs in the inner regions ( 3R eff ) of 32 galaxies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 121 publications
0
33
0
Order By: Relevance
“…The simultaneous extraction of the spectrum of the stellar body of a galaxy and the spectra of its associated star clusters makes it (Côté et al 2001;Pota et al 2013;Forbes et al 2017;Laporte et al 2019;Fahrion et al 2020b). For the brightest galaxy in our sample -KK 197 -five discrete tracers are available.…”
Section: Internal Dynamics Of Kk 197mentioning
confidence: 99%
“…The simultaneous extraction of the spectrum of the stellar body of a galaxy and the spectra of its associated star clusters makes it (Côté et al 2001;Pota et al 2013;Forbes et al 2017;Laporte et al 2019;Fahrion et al 2020b). For the brightest galaxy in our sample -KK 197 -five discrete tracers are available.…”
Section: Internal Dynamics Of Kk 197mentioning
confidence: 99%
“…The relation between GCs and the underlying galaxy stellar population is less straightforward (Forbes & Remus 2018). In general GCs do not necessarily follow the surface brightness distribution and kinematics of the stars (e.g., Brodie & Strader 2006;Coccato et al 2013;Veljanoski et al 2014), although there is growing evidence for red, metal-rich GCs to be tracers of the host galaxy properties (Fahrion et al 2020;Dolfi et al 2020). Therefore we here compare the kinematics of the simulated galaxies and their stellar halos at large radii with PN kinematic results from the ePN.S early-type galaxy survey (Arnaboldi et al 2017, and in prep.…”
Section: Observed Parameters Of Etgsmentioning
confidence: 99%
“…Decades after the pioneering work of Searle & Zinn (1978) demonstrated the potential of GCs as tracers of galaxy formation, new studies began to exploit it (e.g. Côté, Marzke & West 1998;Bekki et al 2005;Rhode, Zepf & Santos 2005;Muratov & Gnedin 2010;Arnold et al 2011;Tonini 2013;Beasley et al 2018;Choksi, Gnedin & Li 2018;Fahrion et al 2020;Ramos-Almendares et al 2020). Theoretical studies of the formation and co-evolution of galaxies and GCs have shown that GCs trace the build-up of L * galaxies across cosmic time (Reina-Campos et al 2019), and that their abundances and ages contain a record of the assembly history of their host (Kruijssen et al 2019a, b;Massari et al 2019).…”
mentioning
confidence: 99%